Children's Songs 20 pieces for keyboard, 20 Stücke für Klavier oder elektronisches Tasteninstrument - Corea, Chick 1941- (Schott, 1994)
Children's Songs is an album by Jazz pianist Chick Corea, released in 1984. Children's Songs mainly consists of short songs with simple themes. There is little development in the pieces, which capture a variety of melodies and moods.